Evaluation of Integrated Business Licensing System in Indonesia Using HOT-fit Model - Masbudi, Handika; Husain, Husain; Lusa, Sofian; Sensuse, Dana Indra; Indriasari, Sofianti; Putro, Prasetyo Adi Wibowo (Universitas Negeri Semarang, 2024)
Purpose: In an increasingly interconnected global economy, there is a growing recognition among governments of the importance of fostering an environment for businesses to thrive. Indonesia has introduced an integrated business licensing system that centralizes and automates the licensing and permitting processes, simplifying the journey for entrepreneurs, business owners, and government agencies. To multiply the benefits and effectiveness of the system, the government must assess the system to establish a firm basis for its ongoing advancement and enhancement. Methods: The evaluation of integrated business licensing system was conducted using the HOT-fit framework with the perspective of government agencies. Their involvement is crucial for effective licensing and supervision processes. Data was gathered through questionnaires and analyzed using the PLS-SEM method. Result: The findings revealed that system quality and service quality significantly influenced user satisfaction, whereas information quality, user satisfaction, organizational structure, and organizational environment positively impacted system usage. The results also showed that system usage and user satisfaction influenced net benefit. These results can be used to improve the system to match the government agencies’ expectations. Novelty: The novelty of this study lies in its research object which is an integrated system. This research provides insights for targeted improvements in technological, organizational, and human aspects of integrated system implementation.